Gallipoli 1915/16. Britanniens bitterste Niederlage - Jacob, Frank (De Gruyter, 2020)
The Battle of Gallipoli was the Britain$1 (Bs most bitter defeat of the First World War. This volume seeks to place the Dardanelles campaign in proper perspective. It situates Gallipoli in the larger context of the First World War, and describes the role played by the (3z(Binconclusiveness(3y (Bof Gallipoli in the national memories of the successor states of the British Empire.s
German